Microstructures: Influence of Direct Laser Written 3D Topographies on Proliferation and Differentiation of Osteoblast‐Like Cells: Towards Improved Implant Surfaces (Adv. Funct. Mater. 42/2014). (7th November 2014) - Hohmann, Judith K.; von Freymann, Georg
<x xml:space="preserve">Abstract</x> The influence of three‐dimensional topographies on viability parameters of osteoblast‐like cells is investigated via a systematic variation of structural parameters. On page 6573 J. K. Hohmann and G. von Freymann report which topographies significantly enhance proliferation and how structural parameters influence cell morphology and differentiation. Cover design by Judith K. Hohmann and Christoph Reinheimer. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>